Neonatal Mortality Rate in Aseptic Neonatal Care Unit of Al-Sadder Teaching Hospital in Missan Province From 2011 to 2014 - Al-Muhsen Ali, Esraa Abd (European Scientific Journal, ESJ, 2016)
Background: The neonatal mortality rate is a key outcome indicator for newborn care and directly reflects prenatal, natal, and postnatal care. Early neonatal deaths are more closely associated with pregnancy-related factors and maternal health, whereas late neonatal deaths are associated more with factors in the newborn‘s environment. Objectives: To estimate the neonatal mortality rate in Aseptic Neonatal Care Unit of Al-Sadder Teaching Hospital in Missan Province during period (2011-2014). To determine the most common causes of death in the neonatal period. Patients and methods: A hospital-based study was done depending on data collected from records of the Aseptic Neonatal Care Unit of Al-Sadder Teaching Hospital in Missan Province to calculate the number of deaths within the neonatal period (0-28 days) that was conducted from 2011 to 2014. The other line of data was collected from Obstetrical Ward by calculating number of live births for the same period. Then Neonatal Mortality Rate is calculated and conducted for each year according to the method recommended by WHO. Results: The neonatal mortality rates were 12.15, 13.51, 16.37 and16.11 in 2011 to 2014 respectively in which there was an increment in mortality rate. The main causes of death were respiratory distress syndrome, birth asphyxia and congenital anomalies. Conclusion: Neonatal mortality rate was high in the Aseptic Neonatal Care Unit of Al-Sadder Teaching Hospital, but it was less than the previous period in Iraq since 1990. These results suggest, that to decrease neonatal mortality, improved health service quality is crucial.